Effect of microstructural characteristics of lightweight aggregate concrete on fracture parameters of three-point bending notched beams. (October 2022) - Wang, Bin; Zhu, Eryu; Zhu, Chunqi; Zhang, Zhu
Highlights: Revealing the meso -scale fracture mechanism of lightweight aggregate concrete. Determining the analytical method of double- K fracture parameters of non-standard beam. The meso -scale model of lightweight aggregate concrete is consistent with the experimental. Studying the effect of meso -scale structural characteristics on fracture parameters. Abstract: The meso -scale model of three-point bending notched beams based on the cohesive force model is developed to study the effect of the meso -scale structural characteristics of lightweight aggregate concrete on the fracture parameters. The python program based on random polygon aggregate generation and placement algorithm is developed, which uses batch insertion of zero-thickness cohesive elements to generate the meso -scale model. The meso -scale models are verified with the relevant experiment. The analytical method for determining the parameters of the double- K fracture model of non-standard three-point bending notched beams is presented. The effects on the macroscopic fracture parameters of the specimens are evaluated by the meso -scale structural characteristics, such as porosity, strength of lightweight aggregate, volume fraction of lightweight aggregate, and shape of lightweight aggregate. The results prove that the meso -scale model is consistent with the experiment, which verifies the reliability of the meso -scale model. The peak load of the specimen decreases by 12.1 % when the porosity increases from 0 % to 6 %. The peak load increases by 14.94 % when the strength of lightweight aggregate increases from 40 % to 120 %. The peak load increases by 32.31 % when the volume fraction of lightweight aggregate increases from 30 % to 60 %. The initial fracture toughness and unstable fracture toughness of different meso -scale structural characteristics first increase and then decrease. The ratio of initial fracture toughness to unstable fracture toughness with different meso -scale structural characteristics to the peak load remains relatively stable. In addition, the relative error between the peak load of the mesoscopic model based on circular aggregate and the experiment is the smallest, which is 2.36 %.